2007
DOI: 10.1093/hmg/ddm012
|View full text |Cite
|
Sign up to set email alerts
|

Success and failure in human spermatogenesis as revealed by teratozoospermic RNAs

Abstract: We are coming to appreciate that at fertilization human spermatozoa deliver the paternal genome alongside a suite of structures, proteins and RNAs. Although the role of some of the structures and proteins as requisite elements for early human development has been established, the function of the sperm-delivered RNAs remains a point for discussion. The presence of RNAs in transcriptionally quiescent spermatozoa can only be derived from transcription that precedes late spermiogenesis. A cross-platform microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
204
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 235 publications
(215 citation statements)
references
References 49 publications
8
204
0
3
Order By: Relevance
“…Twenty-one TUs demonstrated differential expression in spermatozoa from 14 men with consistent and severe teratozo- Each instance of an LTR or LINE repeat in a TU was counted individually. ospermia, a condition in which Ͻ4% of sperm cells are morphologically normal, relative to 17 normal fertile men (25). Of these 21 TUs, 10 had cDNA/EST support for expression in reproductive organs and tissues.…”
Section: Primate-specific Tus Are Preferentially Expressed In the Repmentioning
confidence: 99%
“…Twenty-one TUs demonstrated differential expression in spermatozoa from 14 men with consistent and severe teratozo- Each instance of an LTR or LINE repeat in a TU was counted individually. ospermia, a condition in which Ͻ4% of sperm cells are morphologically normal, relative to 17 normal fertile men (25). Of these 21 TUs, 10 had cDNA/EST support for expression in reproductive organs and tissues.…”
Section: Primate-specific Tus Are Preferentially Expressed In the Repmentioning
confidence: 99%
“…Remarkably, components of the ubiquitin-proteasome pathway, including Ube2j1, were among the most strongly and significantly differentially regulated genes in human teratozoospermic sperm (41), suggesting that Ube2j1's role in spermiogenesis may be conserved in humans. Considering that the genetic causes underlying spermiogenic failure in men are still largely unknown, Ube2j1 and other components of this pathway warrant closer examination and might be useful as diagnostic markers for male infertility in humans in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Jasko et al (1990a) and findings provided a better concept of the biological importance of sperm RNAs, allowing the identification of biomarkers of stallion fertility. The sperm transcriptome has been studied in humans (Ostermeier et al 2002), boars (Kempisty et al 2008;Yang et al 2009) and bulls (Gilbert et al 2007;Bissonnette et al 2009;Feugang et al 2010), and the utility of sperm RNA as a marker of infertility has been explored (Miller 2000;Steger 2001), whereby differences in transcript levels in spermatozoa with different motilities (Bissonnette et al 2009;Lambard et al 2004), as well as between normal and abnormal sperm samples (Platts et al 2007;Steger et al 2003), have been reported. Krawetz (2005) demonstrated that some of the sperm RNAs can be delivered to the oocyte during fertilisation.…”
Section: Introductionmentioning
confidence: 99%